Avaliação química e cinética de degradação in vitro da palma forrageira sob diferentes cultivos no semiárido do Brasil - Gomes, Gil Mario Ferreira (2016)
This study aimed to evaluate the effects of N and P fertilization and harvesting frequency on chemical composition and in vitro degradation kinetics of cactus pear cv. ‘Gigante’. The study was conducted under semi-arid conditions of Quixadá and Tejuçuoca, located in the State of Ceará, Brazil. Analysis was made for nine combinations of N and P with five N levels (10, 70, 100, 130 and 190 kg ha-1 yr-1) and five levels of P2O5 (10; 70; 100; 130 and 190 kg ha-1 yr-1) and two harvesting frequency (annual and biennial). Treatments were arranged in a split plot randomized block design with four replications. N and P levels influenced the chemical and mineral composition and fermentation kinetics parameters of the cactus pear, however, the type of response varied according to the harvesting frequency, locality and the cladode order. DM content of cladodes decreased with rising levels of P applied to the soil, except for the DM content of primary and secondary cladodes under biennial harvesting in Tejuçuoca. Considering the content of CP, NDF, OM and TC, values increased with levels of N and/or P. Some exceptions can be pointed out, such as the reduction in CP content of primary cladodes in both locations and of secondary cladodes in Tejuçuoca with biennial harvest, indicating displacement of nitrogenous compounds from older to younger cladodes. Also, the NDF content of secondary cladodes under annual harvest, in Quixadá; OM content of secondary cladodes under annual harvest, in Tejuçuoca, and TC content of secondary and tertiary cladodes under annual harvest, in Tejuçuoca, decreased with fertilization. The effect of harvesting frequency showed that OM, TC and NDF content of cladodes increased and CP content reduced with biennial harvest in both locations. However, the CP content of primary cladodes in Tejuçuoca was not influenced by the harvesting frequency. In the case of cactus pear plant, DM content under annual crop in both locations was reduced according to levels of P, but in Quixadá, under biennial harvest, there was an increase with N and P levels. Content of CP, NDF and OM increased in response to N and P levels. The exception was found for NDF content under annual harvest in Quixadá and for OM content under biennial harvest, in Quixadá, and annual, in Tejuçuoca. The reduction in TC content with fertilization was associated with increased CP content. The effect of harvesting frequency showed that OM, NDF and TC of cactus pear increased and CP content decreased with biennial harvest, in Quixadá; in Tejuçuoca, there was a reduction in DM content and increase in NDF. Fertilization reduced the content of P and Ca of the cactus pear. The content of Ca decreased more prominently in Tejuçuoca, which reduced the Ca:Pxvi ratio to 9.72:1 with the combination N|P2O5 at 190|10 kg ha-1 yr-1 in the biennial harvest in such locality. The content of Mg, S, Fe and Mn increased with fertilization, except for the Mg content under annual harvest, in Quixadá, and the Fe content, under biennial harvest, in Tejuçuoca. The effect of fertilization on K and Cu contents varied with the harvesting frequency and locality. The effect of harvesting frequency showed higher S content under biennial harvest in both locations. In Quixadá, under biennial harvest, there were lower contents of P, K, Mg and Mn. Under this same condition, in Tejuçuoca, it was found a lower content of Ca and Fe and higher content of Mg, Cu and Mn. The total gas production, digestion rate and the lag time increased with increasing levels of N and P. The exception was verified for total gas production, under annual harvest, in Quixadá. The biennial harvest resulted in lower total gas production and digestion rate in Quixadá. In Tejuçuoca, there was increase in digestion rate and lag time under biennial harvest. Nitrogen fertilization improves the quality of cladodes under annual harvest in both locations and reduces the quality of primary cladodes under biennial harvest in both locations and of secondary cladodes in Tejuçuoca. In the case of cactus pear plant, higher levels of N and P applied result in better quality under biennial harvesting in both locations; in higher content of S and Mn and in higher digestibility in both harvesting frequency and in both locations. Cactus pear was also rich in Ca, K and Fe and deficient in P and Cu. The annual harvest improves the quality of primary and secondary cladodes in Quixadá and of secondary and tertiary cladodes in Tejuçuoca. The annual harvest also improves the quality of cactus pear plant in Quixadá. In Tejuçuoca, the harvesting frequency has less influence on the quality of cactus pear plant and biennial harvest promoted a higher digestion rate. In Tejuçuoca, content of Mg, Cu and Mn were lower under conditions of annual harvest, but, the content of S was lower in both locations in this same harvesting frequency.